The Effect of Leadership Style and Work Stress on Employee Retention at Mulia Godean Convenience Store - Anisa, Rischa Nur; Ruliana, Risma; Putri, Sistalia; Sugiarti, Sugiarti; Syah, Toufan Aldian (DAS Institute, 2025)
This study aims to examine the influence of leadership style and work stress on employee retention at Mulia Godean Convenience Store, Yogyakarta. The research investigates how leadership behavior and psychological pressure affect employees’ intention to remain with the organization. The study employs a quantitative research design using survey data collected from employees through a structured questionnaire. The validity and reliability of the instruments were tested using Pearson correlation and Cronbach’s Alpha. Multiple linear regression analysis was conducted to examine the simultaneous and partial effects of leadership style and work stress on employee retention. The results reveal that both leadership style and work stress significantly influence employee retention. Leadership style shows a positive and significant relationship with employee retention, indicating that effective leadership enhances employees’ willingness to stay. Conversely, work stress exhibits a negative and significant relationship with employee retention, suggesting that increased stress levels reduce employees’ desire to remain with the organization. The model explains 90.8% of the variance in employee retention, indicating strong explanatory power. The findings highlight the importance of developing supportive leadership practices and stress management strategies to maintain employee loyalty. Organizations should foster communication, provide recognition, and implement work-life balance programs to reduce stress and enhance retention. This study contributes to the existing literature by simultaneously analyzing leadership style and work stress as determinants of employee retention within the context of small-scale retail businesses in Indonesia, an area that remains underexplored in current HRM research.